Risk Factor Analysis for Dermatitis Due to Work in Rubber Plantation Farmers - Heru Listiono; Muhammad Romadhon; Siti Aisyah (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2022)
Occupational contact dermatitis is a skin disorder that is often found in rubber plantation farmers. Exposure to chemicals in the process of rubber clumping can cause contact dermatitis, resulting in irritation and other skin disorders in the form of itching, dry and cracked skin. Occupational contact dermatitis is affected by contact duration, personal hygiene, work history, use of personal protective equipment, history of previous skin diseases and years of service. The purpose of this study was to determine the risk factors for the incidence of dermatitis due to work in rubber tapping farmers on wetland rubber plantations. This research is an analytic survey with cross sectional research design, the study was conducted in January 2020 in the Region of East Buay Madang District, Regency of East OKU, South Sumatra, the study sample numbered 73 respondents, through simple random sampling. Data analysis using univariate analysis (proportion), bivariate (chi square test) and multivariate (logistic regression). The results of the analysis show that contact duration (p= 0.013), personal hygiene (p= 0.011), work history (p= 0.001) and the use of Personal Protective Equipment (p= 0.001) have a significant relationship with the incidence of occupational dermatitis, while a history of previous skin diseases (p= 0.097) and years of service (p= 0.95) do not have a significant relationship to the incidence of occupational dermatitis and variable use of Personal Protective Equipment (PPE) is the most dominant variable in causing dermatitis due to work. The results of the analysis found that the variable use of Personal Protective Equipment (PPE) is the most dominant variable in causing dermatitis due to work.